HUBUNGAN VO2MAX DENGAN KELINCAHAN PADA PEMAIN BULUTANGKIS REMAJA - Calvin Muhammad Akbar (2023)
Background: Badminton is the most popular sports games in Indonesia. Badminton has an explosive and fast game character coupled with a rally point playing pattern, so a badminton player needs good strength, agility, cardiorespiratory endurance. The ability of cardiorespiratory endurance can be measured through the maximum volume of oxygen (VO2Max) and will greatly affect the performance of a badminton player when competing. One of the abilities that will be affected is agility. Purpose: This study aims to determine the relationship between VO2Max and agility in adolescent badminton players. Methods: the research method used is a cross-sectional study conducted at one time. A total of 49 youth badminton players participated in this study, the parameters used were the Bleep Test to assess VO2Max levels and the Illinois Agility Test to assess agility levels and SPSS 25 test was also carried out to process existing data. Results: The results obtained were p = 0.001 with a correlation coefficient r = 0.844, which means that there is a significant and unidirectional relationship between VO2Max and agility in youth badminton players. Conclusion: The majority of respondents in this study were male, totaling 44 respondents, with the majority of their VO2Max ability level being in the moderate category, 18 respondents and agility level at an average level of 20 samples and there was a significant and unidirectional relationship between VO2Max and agility at youth badminton player. Keywords: VO2Max, Agility, Bleep test, Illinois agility test